(untitled) (Research, Society and Development, 2022)
The general objective of the study was to investigate the cartographic production of mental health care in the context of Covid-19. A 9-step Scope Review guided by the acronym “PCC” was carried out. The research took place at “Scielo”, “PUBMED”, “LILACS” and “Cochrane”. The descriptors were operated by the automatic boolean identifying only 14 scientific documents, thus presenting a lack of cartographic studies in mental health in the context of Covid-19. Through the inclusion criteria, only 4 documents remained. In the results, a table of key concepts was prepared according to the JBI review protocol model. The studies showed individual and collective support as a way to develop mental health; mutual care; the importance of struggling to continue living through paths of power and development; the reflection of lost lives; the importance of forming care and solidarity networks for neglected populations; and the sharing of stories enabling time-space awareness. Finally, we emphasize the elaboration of new studies against the cartographic model in the understanding of these artifacts that guide social demands.